Immunity in Gilles de la Tourette-Syndrome: Results From a Cerebrospinal Fluid Study - Baumgaertel, Charlotte; Skripuletz, Thomas; Kronenberg, Jessica; Stangel, Martin; Schwenkenbecher, Philipp; Sinke, Christopher; Müller-Vahl, Kirsten R.; Sühs, Kurt-Wolfram (Frontiers in Neurology, 2019)
Background: Several lines of evidence support the hypothesis of an autoimmune origin of Gilles de la Tourette-Syndrome (GTS). Accordingly, in a recent study we detected positive oligoclonal bands (OCB) in cerebrospinal fluid (CSF) in >30% of adult patients indicating an intrathecal antibody synthesis. However, until today no corresponding antibodies could be identified. The aims of this study were to replicate our findings of positive OCB in an independent sample and to detect CSF autoantibodies. Methods: In this prospective study, 20 adult patients with GTS (male: female = 18:2, median age 36.1 years ± 14.34 SD) were included. All patients were thoroughly clinically characterized. Magnetic Resonance Imaging (MRI) and CSF standard measurements were performed. Isoelectric focusing on polyacrylamide gels with silver staining was used to detect OCB. To examine specific and unspecified autoantibodies, we used transfected Human Embryonic Kidney (HEK) cells expressing different surface antigens (NMDA-, CASPR2-, LGI1-, AMPA-, or GABAB1/B), indirect immunofluorescence on different brain tissue sections, and enzyme-linked visualization. Additionally, we differentiated Glioma stem cells SY5Y (human neuroblastoma) using retinoic acid and astrocytes (rat). Results: CSF analyses showed positive OCB (type 2) in 4/20 patients (20%). Using transfected HEK cells we did not find specific surface-autoantibodies. Immunohistochemistry on tissue-sections, SY5Y Glioma stem-cells, and astrocytes showed no specific binding patterns either. Conclusions: Our results corroborate previous findings and demonstrate positive OCB in a substantial number of patients with GTS (prevalence in healthy controls: 5%). Although this is the largest study investigating CSF autoantibodies in GTS using several techniques, we failed to detect any specific or unspecified autoantibodies.